A turn-on near-infrared fluorescent chemosensor for selective detection of lead ions based on a fluorophore–gold nanoparticle assembly1. Issue 12 (21st June 2015) - Wang, Shaozhen; Sun, Junyong; Gao, Feng
<x xml:space="preserve">Abstract</x> A turn-on NIR fluorescent chemosensor of Pb2+ based on a fluorescent fluorophore–AuNP assembly has been reported.